Aspirin and Risk of Gastric Cancer After Helicobacter pylori Eradication: A Territory-Wide Study. (19th January 2018) - Cheung, Ka Shing; Chan, Esther W; Wong, Angel Y S; Chen, Lijia; Seto, Wai Kay; Wong, Ian C K; Leung, Wai K
Abstract: Background: Despite successful H. pylori (HP) eradication, some individuals remain at risk of developing gastric cancer (GC). Previous studies showed that aspirin was associated with a reduced GC risk. However, whether aspirin can reduce GC risk in HP-eradicated subjects remains unknown. We aimed to determine the chemopreventive effect of aspirin in HP-eradicated subjects. Methods: We identified subjects who had received a prescription of clarithromycin-based triple therapy for HP between 2003 and 2012 from a territory-wide health care database. The observation period started from commencement of HP therapy (index date), and the follow-up was censored at the end of the study (December 2015), death, or GC diagnosis. Aspirin use was defined as use once or more often weekly. Subjects who failed HP eradication or were diagnosed with GC within 12 months of HP therapy were excluded. The hazard ratio (HR) of GC with aspirin use was calculated by Cox model with Propensity Score adjustment for age, sex, comorbidities, and concurrent medications. All statistical tests were two-sided. Results: The median follow-up was 7.6 years (interquartile range [IQR] = 5.1–10.3 years), and 169 (0.27%) out of 63 605 patients developed GC. The incidence rate of GC was 3.5 per 10 000 person-years. Aspirin use was associated with a reduced GC risk (HR = 0.30, 95% confidence interval [CI] = 0.15 to 0.61). The risk of GC decreased with increasing frequency, duration, and dose of aspirin (all P trend < .001). Conclusions: Aspirin use was associated with a frequency-, dose-, and duration-dependent reduction in GC risk after HP eradication. The effect was most prominent in those who used aspirin daily or for five or more years.